Pengaruh Kepemimpinan, Stres Kerja, dan Motivasi Kerja terhadap Kinerja Karyawan pada PT Kaldu Sari Nabati Indonesia - Aunia, Sovie; Ali, Mochammad Mukti (Jurnal Nasional Manajemen Pemasaran dan SDM, 2024)
This study explores the impact of leadership, work stress, and work motivation on employee performance in the Production Division at PT Kaldu Sari Nabati, Indonesia. Leadership, work stress, and work motivation are independent variables, while employee performance is the dependent variable in this research. Using a descriptive-verificative quantitative methodology, the study involved 100 employees out of a total population of 2,000, selected using a simple random sampling technique and calculated through the Slovin formula with a margin of error of 10%. Data were collected via questionnaires and analyzed using multiple linear regression. The results show that leadership, work motivation, and employee performance are categorized as high, while work stress falls into the moderate category. Further analysis reveals that leadership, work stress, and work motivation significantly and positively influence employee performance, individually and collectively, with a correlation coefficient of 0.891 and a contribution rate of 79.4%.